Citizenship rights in Malaysia : a constitutional reform - Syed Ahmed Khabir Abdul Rahman,; Shakirah Ahmad Sharifuddin,; Mirza Batrisyia Mohd Hafidz, (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2021)
This paper discusses the law in obtaining citizenship for children in Malaysia. This paper would highlight the relevant laws about citizenship and the problems that lie in our law, arising from the current issues faced by the citizens. It mainly revolves around citizenship by operation of law by virtue of Article 14 of Malaysian Federal Constitution. Two case study is the main pillar of this paper. First, the recent Federal Court decision on illegitimate children born to non-Malaysian mothers. This case dealt with so many interpretations of the provision of the Federal Constitution. Main provision that is disputed between majority and minority judgment is the use of Section 17 Second Schedule, Part III. Second, the issue of children that are born overseas to a non-Malaysian father. This is an on-going High Court suit filed by an NGO (Family Frontiers) and six mothers to seek a declaration that Malaysian women married to foreigners have the right under the Federal Constitution by declaring Article 14(1)(b) read with the Second Schedule, Part II, Section 1(b) of the Federal Constitution is discriminatory and is against the spirit of Article 8 of the FC that prohibits discrimination on the grounds of gender. To tackle the legal problems and discriminations faced by children and Malaysian mothers, this paper would address some aspect of the decision that needs to be reviewed and improved. Towards the end of this discussion, the authors suggest relevant constitutional amendments on Malaysian Federal Constitution in order to protect the rights and welfare of the children as well as to eliminate gender discrimination faced by Malaysian mothers.